Oxytocin as a physiological correlate of dyadic music therapy relationships — a randomized crossover pilot study - Busse, Paula Kristin; Neugebauer, Lutz; Kaschubowski, Götz; Anheyer, Dennis; Ostermann, Thomas (Frontiers in Behavioral Neuroscience, 2025)
RationaleMusic therapy has been in practice for years. However, the mechanism of action of music or music therapy is not well understood. It is only recently that the neuroendocrinological basis of therapeutic relationships has become the subject of growing research interest. The aim of this pilot study (Clinical Trial No: DRKS00035174) is to investigate whether oxytocin is usable and feasible as a biomarker of attachment to demonstrate the development of therapeutic alliance between therapist and patient in a dyadic music therapy setting.MethodsIn a single-measure crossover design, children aged 6–12 years from a special school for social and emotional disorders, were randomly with either music therapy followed by a waiting list control group that performed silent work, or vice versa. The respective interventions were conducted on the school premises on different days over a period of 1 month. The primary outcome was salivary oxytocin, with tests performed immediately before and after each 30-min intervention.ResultsThirty-two children were included in the study, resulting in n = 16 children per allocation sequence. During the implementation of the study, difficulties were encountered with protocol adherence both in terms of the duration of the music therapy and the implementation of the silent work in the control group. There were no dropouts, however, only 28 children were included in the final data analysis as two participants in each group were excluded due to large fluctuations in oxytocin levels. Between-group comparison and within-group comparisons showed no significant changes in oxytocin levels. However, the music therapist showed a significant increase in oxytocin levels in the before after measurement. No side effects or adverse events were reported during the trial.ConclusionThe findings indicated a responsiveness of oxytocin to musical stimulation. Although feasibility of oxytocin measurement was clearly demonstrated, evaluation of the results is difficult against the background of many remaining questions regarding individual and contextual factors influencing the oxytocinergic system. Moreover, the clinical significance of changes in oxytocin levels remains a topic for further research to better understand the role of oxytocin in the attachment formation between therapist and patient in music therapy.